2006
DOI: 10.1063/1.2204759
|View full text |Cite
|
Sign up to set email alerts
|

Branched Ta nanocolumns grown by glancing angle deposition

Abstract: Periodic arrays of Ta nanocolumns, 200nm wide and 600nm tall, were grown by glancing angle sputter deposition onto self-assembled close-packed arrays of 260-nm-diameter silica spheres. Each sphere leads to the development of a single Ta column. As growth progresses, roughening of the column top surfaces causes branching of some columns into subcolumns. The measured fraction of branched columns fb decreases with increasing growth temperature, from 30% at 200°C to 4% at 700°C. This is attributed to the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…OAD, developed by Robbie and Brett, [14] exploits atomic shadowing effects during line-of-sight physical vapor deposition to create arrays of uniquely shaped nanostructures by controlling polar and azimuthal deposition angles. Most reported studies on OAD have focused on the manipulation of various shaped nanostructures such as zigzags, [15] pillars, [16] spirals, [17] slanted posts, [18] columns, [19] with potential applications as magnetic storage media, [20] sensors, [21] actuators, [22] and field emitters. [23] Here, we use OAD to fabricate Ge nanowire arrays that can be controlled from amorphous to polycrystalline and single-crystalline structures by modulating the substrate temperature and evaporation rate.…”
Section: Introductionmentioning
confidence: 99%
“…OAD, developed by Robbie and Brett, [14] exploits atomic shadowing effects during line-of-sight physical vapor deposition to create arrays of uniquely shaped nanostructures by controlling polar and azimuthal deposition angles. Most reported studies on OAD have focused on the manipulation of various shaped nanostructures such as zigzags, [15] pillars, [16] spirals, [17] slanted posts, [18] columns, [19] with potential applications as magnetic storage media, [20] sensors, [21] actuators, [22] and field emitters. [23] Here, we use OAD to fabricate Ge nanowire arrays that can be controlled from amorphous to polycrystalline and single-crystalline structures by modulating the substrate temperature and evaporation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Most GLAD experiments described in literature so far were done at T S ¼ RT, arguing that high T S values would increase the surface diffusion length of the incoming particles, which is undesired for GLAD as it counteracts the self-shadowing process (as a rule of thumb, the ratio of substrate temperature T S to melting point T M of the material to be deposited should be T S =T M < 0:3 for negligible surface diffusion [2,24]). Only few reports concerning the influence of elevated T S on glancing angle deposited nanostructures exist so far [25][26][27][28][29], and none of them discusses the influence of T S on the growth of screw-and spiral-like structures. In the present study, however, the influence of the surface diffusion on the growth of helical structures grown at low and intermediate substrate rotational speed v (with respect to the deposition rate) is evaluated, and it will be shown that T S influences the growth of the structures in terms of merging behavior, film density, and diameter of the structures.…”
Section: Depicts Thementioning
confidence: 99%
“…It is similar to the glancing angle deposition (GLAD) or oblique angle deposition in which there is a large angle between the deposition direction and the normal direction of the substrate. [76][77][78][79][80][81][82][83][84] In the traditional GLAD method, atoms from the target obliquely arrive and condense on the substrate, and the tilted and separated nanowire or nanopillar array with a porous structure are gradually produced due to the shadow effect of the initial deposited nanoparticles under high-vacuum conditions. The critical difference between this route and GLAD is the background gas pressure during deposition, which converts the directional flow of ejected species in a vacuum into a multidirectional one at higher pressure.…”
Section: Formation Mechanism Of Hierarchical Micro/nanostructured Arrmentioning
confidence: 99%